2016
DOI: 10.1186/s40729-016-0061-3
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of 10,000 implants from insertion up to 20 years—analysis of implantations using augmentative procedures

Abstract: BackgroundA sufficient amount of bone is essential to ensure long-term stability of dental implants. To support the bone regeneration process, different techniques and materials are available. It has been questioned whether these techniques and materials may compromise implant survival compared to pristine bone. To properly answer this question, long-term stability up to 20.2 years after insertion of implants placed in augmented or non-augmented sites was retrospectively analysed.MethodsRetrospective analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…Allogenic bone grafts also have an excellent safety profile, as a World Health Organization initiated study demonstrated no reports on transmission of any kind of infectious diseases associated with freeze‐dried bone allografts (FDBA) . Furthermore, the increasing demand for implant‐borne prosthesis is concordant with rising numbers of bone augmentation procedures, as these are often required to provide sufficient bone quantity prior to or with installation of a dental implant …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Allogenic bone grafts also have an excellent safety profile, as a World Health Organization initiated study demonstrated no reports on transmission of any kind of infectious diseases associated with freeze‐dried bone allografts (FDBA) . Furthermore, the increasing demand for implant‐borne prosthesis is concordant with rising numbers of bone augmentation procedures, as these are often required to provide sufficient bone quantity prior to or with installation of a dental implant …”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26][27][28] Furthermore, the increasing demand for implant-borne prosthesis is concordant with rising numbers of bone augmentation procedures, as these are often required to provide sufficient bone quantity prior to or with installation of a dental implant. 5,6 Clinical data on the survival and success rates of allogenic bone blocks are excellent, ranging from 93.7% to 100%, however, allogenic bone blocks were reported to be more technique-sensitive and susceptible to infection when compared to autografts. 17,22 Complications reported with the application of allogenic bone grafts are almost exclusively related to contaminations, which can occur either during the adaptation of blocks to the defect's geometry, or, because of improper soft-tissue management resulting in membrane exposure, incision line opening and perforation of the mucosa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bovine xenografts play a major role and have been proven for cranio‐maxillofacial applications (Yamada & Egusa, ) with no reports on Transmissible Spongiform Encephalopathies (TSE) and Bovine Spongiform Encephalopathy (BSE) risk (Kim, Nowzari, & Rich, ). Results from a large retrospective analysis with long‐term observation time (Knofler, Barth, Graul, & Krampe, ), together with a systematic review of survival data, indicate that synthetic graft materials are associated with lower dental implant survival rates than bovine cancellous bone substitutes (Aghaloo & Moy, ). Nevertheless, in randomized control clinical trials (Mardas, Chadha, & Donos, ; Mardas, D'Aiuto, Mezzomo, Arzoumanidi, & Donos, ) with a synthetic bone substitute or bovine xenograft, both types of BGs presented similar radiographic alveolar bone changes when used for alveolar ridge preservation.…”
Section: Review Of Current Literaturementioning
confidence: 99%
“…Therefore, a very commonly used source of bone matrices is animal‐derived bones; bovine xenografts, distantly followed by equine and porcine, are commonly used in clinical practice. Bovine‐derived cancellous BGs are acknowledged as the closest xenograft to human bone to be regenerated, second only to autografts (Datta, Gheduzzi, & Miles, ; Athanasiou et al., ), and are considered safe products that can be used daily in clinical practices where bone regeneration is needed in reconstructive surgeries (Capanna et al., ; Knofler et al., ). However, necessary cleaning and sterilization processes for starting, raw materials of animal origin result in the decay of both mechanical and biological performances (Vishwakarma, Sharpe, Shi, & Ramalingam, ).…”
Section: Review Of Current Literaturementioning
confidence: 99%